Comparative Effects of 12 Weeks of Center-Based versus Home-Based Exercise Training on hs-CRP and IL-6 Levels in Patients with Heart Failure Reduced Ejection Fraction - Susilo Lawrence, Daniel; Fajar Muzakkir, Akhtar; Patimang, Yulius; Amir, Muzakkir; Djafar, Zaenab; Warliani, Melda; Alfian Zainuddin, Andi (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Heart failure (HF) is a global health concern characterized by significant morbidity and mortality, often associated with chronic systemic inflammation. Exercise-based cardiac rehabilitation is a cornerstone of HF management; however, accessibility limitations often restrict participation. Home-based exercise programs offer a potentially viable alternative. This study aimed to evaluate the effects of 12 weeks of center-based versus home-based exercise training on inflammatory markers, specifically high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6), in patients with heart failure with reduced ejection fraction. Aim. This study aimed to evaluate the effects of 12 weeks of center-based versus home-based exercise training on inflammatory markers, specifically high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6), in patients with heart failure reduced ejection fraction. Materials and Methods. A quasi-experimental design was employed involving 31 patients diagnosed with heart failure with left ventricular ejection fraction below 40 %. Participants were allocated into two groups: center-based exercise (n=15) and home-based exercise (n=16). Both groups underwent a 12-week exercise rehabilitation program consisting of light-intensity sessions five times per week. Baseline and post-intervention blood samples were collected to measure serum levels of hs-CRP and IL-6. Clinical and demographic data were also recorded. Statistical analyses were performed using the Mann–Whitney and Wilcoxon signed-rank tests, with significance set at p<0.05. Results and Discussion. Both exercise modalities resulted in significant reductions in IL-6 and hs-CRP levels after 12 weeks (p<0.001). Median IL-6 decreased from 13.1 pg/mL to 4.8 pg/mL, while median hs-CRP declined from 4.3 mg/L to 2.5 mg/L across all participants. No statistically significant differences were observed between the center-based and home-based groups in the extent of reduction for either biomarker (IL-6, p=0.906; hs-CRP, p=0.200). Conclusions. Twelve weeks of home-based exercise training is as effective as center-based training in reducing systemic inflammation, as measured by IL-6 and hs-CRP, in patients with heart failure with reduced ejection fraction. These findings support the use of home-based rehabilitation as a viable alternative to center-based programs for managing inflammation in this patient population.